DEVELOPMENT OF SPEED-STRENGTH QUALITIES IN FOOTBALL PLAYERS AT THE ADVANCED SPECIALIZATION STAGE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article presents theoretical information and practical recommendations for developing the speed-strength qualities of football players.